Application of the Peruvian Arc for high stress mining Sub Level Caving – Yauricocha Mine - Curasma Ramos, Gamaniel (2023)
At the Yauricocha mine, there is an issue where the steel ribs used in the production stopes fail within a period of less than two months. This leads to an increase in support costs and delays in ore extraction, as the mining operations have to be halted for the reinstallation of the steel ribs.Furthermore, this can even result in ore loss. These problems arise due to the generation of high stresses caused by the massive mining technique known as Sub Level Caving. In the production stopes, it is necessary to maintain a minimum operational section of 3.0 meters to accommodate the entry of the 6-cubic-yard low-profile loaders. This compliance ensures ore recovery. To achieve this objective, a new support design is proposed formining. The Peruvian arch is a reinforced concrete arch element with high-strength structural steel placed between the steel ribs in the production stopes of the Yauricocha mine. Currently, it is being applied in the production stopes of the Esperanza zone, successfully recovering the ore andyielding savings of over $2300 per every 10 meters of mining.